303 Longitudinal arrhythmic risk assessment based on ejection fraction in patients with recent-onset non-ischaemic dilated cardiomyopathy. (8th December 2021) - De Angelis, Giulia; Merlo, Marco; Barbati, Giulia; Bertolo, Silvia; De Luca, Antonio; Ramani, Federica; Adamo, Luigi; Sinagra, Gianfranco
Abstract: Aims: Practice guidelines suggest implantable cardioverter defibrillators (ICD) in patients with left ventricular ejection fraction (LVEF) ≤35% despite 3–6 months of guideline-directed medical therapy (GDMT). It remains unclear whether this strategy is appropriate for patients with dilated cardiomyopathy (DCM), who can experience reverse ventricular remodelling for up to 24 months after initiation of GDMT. We sought to assess the longitudinal dynamic relationship between LVEF ≤35% and arrhythmic risk in patients with recent onset non-ischaemic DCM under GDMT. Methods and results: We performed a competitive risk analysis on patients with recent onset DCM (≤6 months) and recent initiation of GDMT (≤3 months), consecutively enrolled in a longitudinal registry. We assessed risk of major ventricular arrhythmic events or sudden cardiac death (MVAs/SCD) in relationship to LVEF ≤35% at enrollment, 6-months and 24-months post initiation of GDMT. 544 patients met inclusion criteria. LVEF ≤35% identified patients with increased risk of MVAs/SCD starting from 24-months after initiation of GDMT (hazards ratio: 2.126, 95% confidence interval: 1.065–4.245, P = 0.03). However, LVEF ≤35% at presentation or at 6 months post enrollment did not have prognostic significance. 67% of patients with LVEF ≤35% at 6 months after initiation of GDMT improved their LVEF to > 35% by 24 months. This late LVEF improvement correlated with a lower arrhythmic risk ( P = 0.012) and was preceded by a reduction of LV dimensions in the first 6 months of GDMT. Conclusions: In patients with DCM, risk stratification based on LVEF ≤35% is effective after 2 years of GDMT, but not after 6 months.